Vocabulary in textbooks for young learners - Marie Nordlund (Educare)
An extensive vocabulary is necessary for successful communication in a foreign language. According to the Swedish National Agency for Education, the teaching of English in Sweden is often based on one textbook and on that textbook only. The purpose of this study is therefore to describe what vocabulary is presented in one teaching material aimed at school years 4–6 (age group 10–12 years) in Sweden. More precisely, the following questions have been considered: (i) what are the most frequent words in the textbooks? and (ii) to what extent do words recur in the textbooks? To answer these questions, a corpus of the texts in the three books was compiled. The analyses show that although the texts appear to have been chosen to appeal to the age groups aimed for, there does not seem to be any consciously considered rationale behind the choice of what vocabulary to include, many words occur only once and the necessary repetition of words is thus lacking.